20‐Year Trajectories of Substance‐Use Service Utilization by Ontario's Muslim‐Majority Country Immigrants - Ahmed N. Hassan; Fardowsa Ahmed; Haley Golding; Luke Mondor; Taaha Muhammad; Marwa Azab; Jibran Khokhar; Heba Ragheb; Allie Ali; Nazila Isgandarova; Abd Alfatah Tawakkal; Refik Saskin (Psychiatric Research and Clinical Practice)
Objective The aim of this study is to conduct a population‐level study on substance use treatment utilization among immigrants from Muslim‐majority countries (MMC) and non‐MMC, compared with Canadian‐born individuals in Ontario. Methods A population‐based, repeated measures cross‐sectional study was conducted. Additionally, individuals with at least one contact with substance use services were followed. Negative binomial models were run to compare the rate ratio of the number of repeated healthcare visits per person per year of follow‐up by subpopulation group. This study included three separate populations (Canadian‐born, immigrants from MMC, and immigrants from non‐MMC) residing in Ontario, Canada. All individuals residing in Ontario on the first day of each calendar year from January 2003 to December 2022 were included. Data were collected from three major sources: outpatient visits, emergency department visits, and inpatient hospitalizations. Results In 2022, immigrants from MMC (n = 561,937) and non‐MMC (n = 2,138,307) groups had lower substance‐use service utilization across all service types compared with Canadian individuals (n = 12,178,607). Comparing 2022 to 2003, the most significant increase in utilizing hospitalization was for MMC immigrants (RR: 3.0; 95% CI: 2.1–4.4; p < 0.01) and the lowest increase in outpatient service utilization was in MMC immigrants (RR: 1.8; 95% CI: 1.5–2.0; p < 0.01). The rates of repeated service utilization among those who initiated contact with outpatient services in the MMC and non‐MMC groups were significantly less than Canadian‐born individuals. Conclusions Immigrants from MMC and non‐MMC with substance use disorders may utilize service only at critical stages, thereby jeopardizing treatment success.